Análise bibliométrica da produção científica brasileira sobre suicídio: um estudo nas bases de dados Scopus e OpenAlex - Zanin, Alda de Cássia (Universidade Federal de São Carlos, 2025)
This research analyzed Brazilian scientific production on suicide, aiming to understand its academic approach and identify relevant trends, authors, institutions, journals, and thematic areas. To this end, a quantitative bibliometric research methodology was adopted, using bibliographic data from the Scopus and OpenAlex databases, processed by the VOSviewer and Biblioshiny tools to construct indicators of production, citation, and linkage. The results revealed significant growth in publications from 2010 onwards, especially between 2020 and 2021, with an emphasis on mental health, social vulnerability, and clinical-epidemiological studies. International cooperation is noteworthy, particularly with the United States, the United Kingdom, Portugal, and Canada. Among the most productive authors are Flávio Kapczinski, Neury Botega, Antonio Egídio Nardi, Maria Cecília Minayo, Karen Jansen, and Humberto Correa, and among the most frequently cited journals are Ciência e Saúde Coletiva, Revista Brasileira de Psiquiatria, and Jornal Brasileiro de Psiquiatria. The University of São Paulo leads the production, followed by other reference institutions, and the central areas of publication focus on Medicine, Psychology, Psychiatry, and Sociology, confirming the interdisciplinary nature of the topic. It was concluded that national research emphasizes mental disorders, vulnerable groups, social and environmental factors, epidemiological contexts, and manifestations of suicidal behavior, highlighting the relationship between psychological suffering, suicide risk, and impact on work. The study evidenced the need for responsible communication about suicide, grounded in scientific rigor and neutral language, in order to support health professionals, communicators, and managers in prevention and in strengthening support networks, such as the Center for Life Appreciation (CVV). Furthermore, it demonstrated the relevance of bibliometrics for Library and Information Science, by applying its tools to the analysis of a sensitive topic, and pointed to the importance of future qualitative research integrating mental health, communication, and information management, expanding support for the formulation of more effective public policies.
Bibliometric analysis of brazilian scientific production on suicide: a study in the Scopus and OpenAlex databases.
Keywords: Suicídio; Análise bibliométrica; Produção científica; VOSviewer; Bibliometrix; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA; 3. Saúde e Bem-Estar